Taxonomy and distribution of caecilian amphibians (Gymnophiona) of Brazilian Amazonia, with a key to their identification - Maciel, Adriano O.; Hoogmoed, Marinus S. (Zootaxa, 2011)
Based on examination of 622 specimens of Gymnophiona, 15 species are recognized for Brazilian Amazonia. Geographical variation in characters is low and is mainly restricted to the number of annuli. One new species is described, Microcaecilia rochai sp. nov. New distribution data and maps for most species are provided. A key to the identification of caecilians of Brazilian Amazonia is presented.